Pengembangan Aplikasi Kriptografi Modern Menggunakan Algoritma Simetris DES Berbasis Python - Khairani, Lisda; Jasmiati, Jasmiati; Siregar, Putri Hasanah; Berutu, Putri Kenangan Br; Manurung , Andhika Saputra; Samosir, Alif Saka Al Bani (JIKUM: Jurnal Ilmu Komputer, 2025)
In the current digital era, the security of information has become a fundamental aspect of system development. Cryptography, especially symmetric key algorithms, plays a key role in protecting data confidentiality. This research presents the development of a modern cryptographic application based on the Data Encryption Standard (DES), implemented using the Python programming language. The system is equipped with a graphical user interface (GUI) developed using Tkinter, allowing users to easily encrypt and decrypt text data. In addition to DES, the application also includes educational features such as RSA encryption and SHA-256 hashing to enhance users' understanding of various cryptographic techniques. The development process follows a prototyping method, from initial analysis to implementation and testing. Several functional tests were conducted using various text inputs, and results showed that the application successfully performed accurate encryption and decryption. Furthermore, the GUI interface provides an intuitive user experience, making it suitable as a learning tool in educational environments. This research contributes to the field of computer security by offering an open, accessible tool for understanding classical encryption methods and promoting awareness of basic data protection strategies in software applications.